OpenSimRoot: widening the scope and application of root architectural models - Postma, Johannes A.; Kuppe, Christian; Owen, Markus R.; Mellor, Nathan L.; Griffiths, Marcus; Bennett, Malcolm J.; Lynch, Jonathan P.; Watt, Michelle (Wiley, 2017)
Research Conducted and Rationale: OpenSimRoot is an open sourced, functional- structural plant model and mathematical description of root growth and function. We describe OpenSimRoot and its functionality to broaden the benefits of root modeling to the plant science community.